2015
DOI: 10.1111/jar.12215
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Supports of People with Intellectual Disability and Their Families in Catalonia

Abstract: Besides providing specific support for individuals with intellectual disability, local policymakers and practitioners should apply a family-centred approach to the provision of support for families in order to improve FQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
2
15
0
6
Order By: Relevance
“…Although various skills were described, everyone agreed that all people with ID require at least some support from others. This is congruent with previous studies (Hale et al, ; Vilaseca et al, ). Even though staff reported that a small minority of their clients might not feel the need to become more independent, staff, and legal representatives expressed that most people with ID would have both the desire and the ability to become more independent.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although various skills were described, everyone agreed that all people with ID require at least some support from others. This is congruent with previous studies (Hale et al, ; Vilaseca et al, ). Even though staff reported that a small minority of their clients might not feel the need to become more independent, staff, and legal representatives expressed that most people with ID would have both the desire and the ability to become more independent.…”
Section: Discussionsupporting
confidence: 94%
“…Most people with intellectual disabilities (ID) struggle with managing their affairs independently (Ramdoss et al, 2012;Sigafoos et al, 2005) and are therefore often at least somewhat dependent on the support from family and care staff (Hale, Trip, Whitehead, & Conder, 2011;Vilaseca et al, 2017). The struggles of people with ID can range from difficulties with personal care and household activities, to trouble with community participation and employment (Dusseljee, Rijken, Cardol, Curfs, & Groenewegen, 2011;Ramdoss et al, 2012;Smith, Shepley, Alexander, & Ayres, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Em consonância com outras pesquisas 49,57,58,59 , nosso estudo revelou que os deficientes recebem menos serviços e suportes do que realmente necessitam, nas áreas de saúde, educação e lazer. Políti-Cad.…”
Section: Discussionunclassified
“…This can pertain to many aspects of daily living, from taking care of their personal hygiene and their household, to dealing with social interactions and employment (Dusseljee, Rijken, Cardol, Curfs, & Groenewegen, ; Smith, Shepley, Alexander, & Ayres, ; Van Laarhoven & Van Laarhoven‐Myers, ). Therefore, people with intellectual disabilities often have to rely on others (Hale, Trip, Whitehead, & Conder, ; Vilaseca et al., ). This does not only pose everyday challenges for these individuals, but also for their families and health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, as this could enhance their overall quality of life and their participation and inclusion as equal and valued co‐citizens (Dollar, Fredrick, Alberto, & Luke, ; Sigafoos et al., ), which could lead to reductions in behavioural problems (García‐Villamisar, Dattilo, & Matson, ). Furthermore, it could decrease their demand for professional care and the burden that is experienced by family members (Dawson et al., ; Vilaseca et al., ).…”
Section: Introductionmentioning
confidence: 99%